North-South cooperation in higher education: Potentials and limitations : the case of the Eastern African-Austrian AQUAHUB programme - Margarita Langthaler; Arnold Groh; Stefan Wolf; Oskar Kabbeck; Gerold Winkler (Austrian Foundation for Development Research (ÖFSE), 2024)
Cooperation between institutions of higher education in North-South directions have long been a common instrument of development cooperation in the education sector. At the level of research, North-South partnerships have increasingly become a preferred strategy of financing mechanisms for research on and in countries of the global South. Transnational cooperation and partnership projects are considered to be particularly useful for capacity building at institutions in the global South. For this to materialise, however, several preconditions, such as long-term commitment, trustful relationships and accounting for power asymmetries as well as contextual factors, need to be in place, as recent research on the Eastern African-Austrian AQUAHUB programme confirms.
Keywords: 330; North-South-cooperation in higher education; capacity development; equitable partnerships